THU0158 'ONE IS NOT ENOUGH' - RITUXIMAB SINGLE VS DOUBLE INFUSION PROTOCOL IN TREATMENT OF ESTABLISHED RHEUMATOID ARTHRITIS – REAL LIFE EXPERIENCE OF GARTNAVEL GENERAL HOSPITAL, GLASGOW, UK. (2nd June 2020) - Batool, S.; Abdullah, M. A.; Anderson, K.; Bawa, S.
Abstract : Background: Rituximab (RTX), chimeric anti-CD20 monoclonal antibody, is recommended as a treatment option for rheumatoid arthritis (RA) patients who had inadequate response or are intolerant to other DMARDs including at least one anti-TNF inhibitor 1 . The most cost-effective dosing and retreatment schedule remains to be defined. Based on series of case reports and observational studies, it is suggested that retreatment with RTX 1g single infusion provides similar clinical outcomes compared with 2 x 1g infusions 2 . We report our experience of using single infusion in treatment of established RA. Objectives: Our unit adopted the single 1g infusion protocol in 2017. Patients were switched to RTX biosimilar – in September 2017. The aim of this study was to assess the effectiveness of single 1g infusion in maintaining the response in RA patients. Methods: 80 established RA patients on RTX were identified using clinical records held on our database. 67.50% (54/80) were on single 1g infusion and 28.75% (23/80) were receiving 2 x 1g infusions. Flare and inadequate response were assessed by comparing DAS scores pre and post RTX treatment and clinical judgement. We also assessed the effectiveness of biosimilar RTX, and in switching to biosimilar RTX. Results: RTX group: Overall retention rate was 57.41% (31/54) in single infusion retreatment group. 31.48% (17/54) flared and 76.47% (13/17) were switched back to 2 x 1g infusions with recapture of response in all patients. 1 patient continued single infusion due to recurrent cytopenia and 3 have not had retreatment yet. 11.11% (6/54) had secondary loss of effect (LOE). No flares were noted in 2 x 1g infusion group. 3.75% (3/80) had severe anaphylactic reaction needing to stop their treatment whereas 5% (4/80) experienced minor infusion reactions but managed to continue their treatment. Switch group: 52 patients switched from RTX to biosimilar. 42 received single 1g infusion and 10 had 2x1g infusions. In single infusion group, 53.38% (22/42) maintained response, 33.33% (14/42) flared with recapture of response in 92.86% (13/14) on 2x1g infusions and secondary LOE in 11.90% (5/42). In 2x1g infusion group, 90% (9/10) maintained response whereas 10% (1/10) had secondary LOE. Biosimilar RTX group: There were 25 patients on biosimilar RTX. 13/25 (52%) went onto single 1g infusion retreatment protocol. Of these, 3 (23.07%) had flare and 1 (7.69%) had secondary LOE. There were 6 (24%) primary response failures, 2 (8%) minor infusion reactions and 1 (4%) major infusion reaction in this group. Conclusion: One third of patients in our cohort failed to respond to single infusion protocol. These results were reproducible in all groups – RTX, switch and biosimilar RTX single infusion group. Our study suggests clinicians and patients need to be vary in using single infusion protocol as there is significant risk of losing disease control. References: [1]Adalimumab, etanercept, infliximab, rituximab and abatacept for the treatment of rheumatoid arthritis after the failure of a TNF inhibitor. Available at: https://www.nice.org.uk/guidance/ta195/chapter/1-Guidance [2]Dougados M, Combe B, Le Loët X, et al. THU0087 One single infusion of rituximab 1g might be sufficient in the long-term management of rheumatoid arthritis patients responding to a first cycle of rituximab (2 × 1g): Results of a 2-year multi-center randomized controlled trial. Annuals of the Rheumatic Diseases 2013; 71:182 Acknowledgments: Rheumatology Department, Gartnavel General Hospital, Glasgow, UK Disclosure of Interests: None declared